1984
DOI: 10.1007/bf00007195
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration of streams draining clearcut watersheds: Quantification and biological implications

Abstract: A quantitative evaluation of stream temperature alterations due to a commercial forest harvesting practice and a research treatment is presented. Summer maximum stream temperatures averaged I C higher in the commercial clearcut and 9 °C higher in the clearcut-herbicided watershed than in the forested control. The largest average monthly temperature increase on the commercial clearcut (2.2 C) occurred during April; on the clearcut-herbicided basin it occurred during June (10.5 C). Significant changes in stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 10 publications
4
40
0
2
Order By: Relevance
“…These high water temperatures apparently cause a decline in DO levels in the summer months in Bayou Plaquemine Brule. In a forest system, greater diurnal variation of stream temperatures are reported in those streams where clear-cut harvesting rather than patch-cutting was practiced (Lynch et al 1984). Clearance of streamside 0 .08* 1 (n = 986) Cond.…”
Section: Resultsmentioning
confidence: 99%
“…These high water temperatures apparently cause a decline in DO levels in the summer months in Bayou Plaquemine Brule. In a forest system, greater diurnal variation of stream temperatures are reported in those streams where clear-cut harvesting rather than patch-cutting was practiced (Lynch et al 1984). Clearance of streamside 0 .08* 1 (n = 986) Cond.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the observed temperature measurements could be extracted; exceptions were two studies presenting temperature change between upstream and downstream [25,26] or one study presenting temperatures change from a forest control [27]. Effect sizes from studies were calculated as the difference between average temperature in the streams with trees and average temperature in streams without trees in the riparian zone (or difference in the temperature change in the case of the three studies cites above).…”
Section: Data Extraction Strategymentioning
confidence: 99%
“…Ten articles were identified following full text assessment, and from which data could be retrieved [23][24][25][26][27][29][30][31][32][33]. These studies were conducted in USA (4), Canada (3), New Zealand (2) and UK (1).…”
Section: Groupmentioning
confidence: 99%
“…Diurnal fluctuations in temperature of 5°C are common in many headwater streams, especially those draining recently clear-cut catchments or catchments with sparse canopies. Lynch, Rishel & Corbett (1984) found that while average monthly diel fluctuations in temperature ranged from 0.9 to 2.7°C and never exceeded 6°C in a forested catchment in Pennsylvania, diel fluctuations of 6°C or more were observed from as early as March to as late as November in a clearcut basin. In addition, diel variations exceeded H 0 C on 18 days in June and 11 days in July in the clear-cut catchment.…”
Section: Discussionmentioning
confidence: 93%